Thực trạng trường mầm non công lập chất lượng cao theo hướng tự chủ trên địa bàn thành phố Hà Nội - Thân Văn Quân, Thân Văn Quân; Đinh Bích Hà, Đinh Bích Hà (Tạp chí Giáo dục, 2026)
Researching and applying modern school models is one of the important tasks in response to the requirements of fundamental and comprehensive educational innovation in our country today. High-quality public schools in the direction of autonomy are schools that are receiving much attention from society. In recent times, they have had strong development, initially affirming their advantages in ensuring educational quality. This article presents the content of the assessment of the current status of autonomy in high-quality public preschools. Based on the results of surveys, exchanges, interviews, consultations with experts, and research of summary reports, it shows that highquality public preschools in the direction of autonomy in Hanoi city have currently had strong and comprehensive development in all aspects; the conditions of autonomy have been attached and created favorable conditions for ensuring high quality; however, the development process still has certain limitations.